2002
DOI: 10.1088/0963-0252/11/1/305
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved gas temperature measurements by Rayleigh scattering in a microwave discharge

Abstract: Rayleigh scattering is used in order to deduce the gas temperature from neutral density measurements inside a microwave discharge in argon. Rayleigh scattering is a powerful non-intrusive method which provides direct heavy particle density measurements with a very high spatial resolution. The gas pressure ranges from 1 to 40 torr and the microwave power ranges from 35 to 900 W. We show that temperature gradient is very sharp at the edge of the plasma column: T g drops to nearly room temperature within 3 cm. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
2
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 25 publications
4
32
2
1
Order By: Relevance
“…The current study can be seen as an extension of the work reported in reference [19] on RyS measurements performed in our laboratory on a SWD delivered by a group from Orsay (Paris-Sud). There are three essential differences:…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…The current study can be seen as an extension of the work reported in reference [19] on RyS measurements performed in our laboratory on a SWD delivered by a group from Orsay (Paris-Sud). There are three essential differences:…”
Section: Introductionmentioning
confidence: 74%
“…The results found in reference [19] based on the DECsimilarity law raised some questions. The shape of the axial dependence of the central values of the T a was found to be composed of two branches: a constant (plateau) value close to the launcher and a steep decay close to the plasma end.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations